Forge of Personnel, Protective Means and Weaponry for the Victory in 1945: the Military Academy of Chemical Defence during the Great Patriotic War - I. A. Samolyga; E. A. Chugunov; A. P. Dzyubenko; I. P. Polishchuk; T. A. Samolyga (Вестник войск РХБ защиты, 2025)
Highlights During the Great Patriotic War (1941–1945) the Military Academy of Chemical Defence (nowadays the Nuclear Biological Chemical Defence Military Academy Named after Marshal of the Soviet Union S.K. Timoshenko (Kostroma)) 1428 competent chemical corps officers. Academy inventions gave the opportunity to create 17 new samples of chemical protection means and to write 17 manuals on chemical corps tactics, which had been actually applied in combat operations. Relevance. It is crucial to analyze the contribution of the Academy to the Victory, if we want to preserve historical memory and prevent history distortion. The academy successfully combines learning process, research and practical application of its inventions in combat conditions. Purpose of the study is to systematize and analyze the contribution of Military Academy of Chemical Defence to the military staff training, chemical protective means development and their practical application during the Great Patriotic War. Study base sources. The authors of this paper have analyzed the records of the central archive of the Ministry of Defence of the Russian Federation, orders and guidelines of people's commissariat of defence of the Soviet Union for the period of 1941–1945, Chemical Corps reports and dispatches from the battlefield, academy graduates recollections and  photographic documents of the war period. Method. Descriptive method. Results. The authors of this paper have found out that 93% of people who graduated from the academy were sent to the front line and 47% out of this number have been awarded with state rewards. It have been confirmed that 23 academy inventions were introduced into military practice in 1942–1944. The Soviet Union troops were quite prepared for the chemical war that is why the Wehrmacht was afraid to use poison gas against them.Conclusions. In the war period the academy ensured regular training of chemical troops experts, created powerful chemical protection system for the Red Army of Workers and Peasants of the Soviet Union, helped to frustrate the plans of the enemy in terms of chemical warfare agents use and saved many thousands of Soviet soldiers.